ANALISIS KECEPATAN TRANSFER DATA NIRKABEL PADA LOCAL AREA NETWORK (LAN) DI JURUSAN TEKNIK ELEKTRONIKA FAKULTAS TEKNIK UNIVERSITAS NEGERI PADANG - Elsi Puspita Sari; Muhammad Adri; Khairi Budayawan (Universitas Negeri Padang, 2014)
Indoor access point (AP) causes the signal quality is reduced because it is hampered by a wall to access the outdoors. Wi-Fi is available for students only 3 APs, and IP availability is limited so it cannot meet all demand access. In addition, all the AP are connected only through the router without using the AP controller that can cause boottleneck. The lack of rule governing UNP Wi-Fi channel Processing, because the Wi-Fi is adjacent even the Wi-Fi uses the same channel so it can causes interference. The purpose of this study is to determine whether available Wi-Fi can cover areas in blocks of Electronical Engineering Department, to know the quality of the signal with InSSIDer Software Network Stumbler and, to know the results of the speed of traffic data at any Available Wi-Fi the Department of Electronical Engineering, and find out if an Access Point (AP) which affects the quality of the indoor signal to access the outdoors. This study classified into the descriptive study with a qualitative approaching using descriptive methods. Sampling technique in this study were 95 users whose population are Electronical Engineering and Electrical Engineering from 2009 to 2012 generation. The technique of collecting data was using questionnaires and observation. Data were analyzed by using the formula. The analysis shows that the network quality is good and no signal quality percentage below 50 %. Throughput values ​​for the uplink and downlink speeds are not always the same, regardless of the size of the data is same. Free Space Path Loss value’s depends on the distance of the user and access point. The greater the distance of the user to the AP the greater Multi Router Traffic Grapher (MRTG). It can be concluded that the average daily traffic, weekly, monthly, and yearly are differerent for the next daily, weekly, monthly, yearly trafics because it depends on the users and conditions. The Wi-Fi’s facility has a very important role to help students to fullfil their needs. Keywords : Wi-Fi, LAN, Throughput, Free Space Path Loss , MRTG.